1973
DOI: 10.1161/01.str.4.2.139
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Regional Autoregulation in the Cerebral Circulation to Increased Perfusion Pressure in Normocapnia and Hypercapnia

Abstract: Catheterization of Labbé's vein and of a pial branch of the middle cerebral artery has been performed on anesthetized baboons. Closure of the skull has enabled the reaction of the venous outflow from Labbé's vein to be monitored in response to pressure step increases in the pial arterial pressure induced by gas compression of a perfusion mixture connected to the arterial line. Rapid changes in cerebrovascular resistance with swift emergence of regulatory constancy have been shown, and the time characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 31 publications
7
72
0
Order By: Relevance
“…A study in apes, using sharp induced upward ABP stimuli, also found such very strong and rapid autoregulatory responses. 1 The dynamic cerebral autoregulation seems to prioritize protection against the imminent danger of cerebral hemorrhage that may accompany upward spike ABP. Ischemia and infarctions, which are the primary dangers of hypoperfusion, would develop over a longer time scale, and more time would be available for compensatory action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in apes, using sharp induced upward ABP stimuli, also found such very strong and rapid autoregulatory responses. 1 The dynamic cerebral autoregulation seems to prioritize protection against the imminent danger of cerebral hemorrhage that may accompany upward spike ABP. Ischemia and infarctions, which are the primary dangers of hypoperfusion, would develop over a longer time scale, and more time would be available for compensatory action.…”
Section: Discussionmentioning
confidence: 99%
“…This physiological control system is remarkably effective, any deviations are rapidly compensated for, 1,2 and the steady-state cerebral blood flow is kept remarkably constant. 3 In patients recovering from head injuries, the cerebral autoregulation mechanism may become impaired, leaving the brain exposed to the vagaries of blood pressure fluctuations, possibly adding to the damage caused by the initial trauma.…”
mentioning
confidence: 99%
“…34 A fast dynamic response to changes in pressure pulsations is followed by a slow static response that restores cerebral blood flow after the initial dynamic response has settled 35 by myogenic (mechanogenic) and metabolic (chemogenic) mechanisms. 36 With decreasing BP, there is vasodilation of arterioles until maximal vasodilation occurs, and subsequently, there is reduction of blood flow. With increasing BP, there is progressive vasoconstriction of arterioles until the BP exceeds the upper limit of autoregulation, followed by breakthrough vasodilation, increase in cerebral blood flow, 36 blood-brain barrier dysfunction, and cerebral edema.…”
Section: Cerebrovascular Physiology and Implications For Treatmentmentioning
confidence: 99%
“…Although that many studies selected ~0.1Hz as an upper frequency boundary in the transfer function analysis, such choice of frequency range for the estimation of cerebral autoregulation is somewhat arbitrary. Previous studies showed that after a sudden blood flow decline, baseline levels can be restored within 3-6 seconds (corresponding to 0.16-0.33Hz in frequency domain) [53,54], and therefore there is no reason to refute the notion that cerebral autoregulation can operate at frequencies >0.1Hz. Studies of using phase synchronization technique and transfer function analysis also indicated that the relationship between BP and BFV oscillations at frequency >0.1 is altered in patients with strokes and, thus, may also provide useful information on cerebral autoregulation [48,55].…”
Section: B Active Frequency Range Of Cerebral Autoregulationmentioning
confidence: 99%